2013
DOI: 10.1186/1752-1947-7-208
|View full text |Cite
|
Sign up to set email alerts
|

Brain and lung metastasis of Bartholin’s gland adenoid cystic carcinoma: a case report

Abstract: IntroductionAdenoid cystic carcinoma of Bartholin’s gland is a very rare disease.Case presentationA 48-year-old premenopausal woman of Caucasian origin was delivered adjuvant pelvic and inguinal radiotherapy after prior complete left Bartholin’s gland tumor excision and inguinal lymph node dissection for adenoid cystic carcinoma of Bartholin’s gland with one metastatic inguinal lymph node.Two years after primary treatment, she presented to the Emergency Room with acute headache, hypoacousia, decrease in visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 10 publications
0
21
0
1
Order By: Relevance
“…Chemotherapy with 5-fluorouracil, cyclophosphamide, methotrexate, doxorubicin, dactinomycin, irinotecan, have been tried in individual cases, but the efficacy of each is difficult to assess due the rarity of this condition and relatively long survival without treatment. Ramanah et al [11] described a patient with confirmed brain and lung metastasis from ACC-vulva, treated with brain radiotherapy, lobectomy and chemotherapy with cyclophosphamide, adriamycin and cisplatin whose disease progressed to death.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy with 5-fluorouracil, cyclophosphamide, methotrexate, doxorubicin, dactinomycin, irinotecan, have been tried in individual cases, but the efficacy of each is difficult to assess due the rarity of this condition and relatively long survival without treatment. Ramanah et al [11] described a patient with confirmed brain and lung metastasis from ACC-vulva, treated with brain radiotherapy, lobectomy and chemotherapy with cyclophosphamide, adriamycin and cisplatin whose disease progressed to death.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of ACCBG is unknown, though a series of ACCBG cases by Copeland has suggested that pregnancy may be an independent risk factor [11]. ACCBGs can present as both painless and painful masses [10, 12] and are usually solitary and unilateral. Clinically, they are associated with pruritus and a burning sensation, which reflects its nature to invade the perineum but has also presented with bleeding, dyspareunia, and discharge from abscesses [13].…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical staining may reveal low-molecular-weight keratins, carcinoembryonic antigen, lysozyme, alpha-antichymotrypsin, S100, and type IV collagen [ 11 ]. Ramanah et al took a step further by performing specific antibody stains of brain metastases from BG-ACC, which revealed positive cytokeratin (CK) AE1/AE3, CK7, and epithelial membrane antigen (EMA); weakly positive S100 and progesterone receptor; and negative CK20 and estrogen receptor [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bones and lungs are the most common site of metastasis; other sites reported are liver, kidney, and brain [ 25 ]. Late recurrences and metastases are associated with poor prognosis [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%